In Vitro Studies on the Inhibition of Colon Cancer by Butyrate and Polyphenolic Compounds. - Goncalves, Pedro; Araujo, Joao R.; Pinho, M. Joao; Martel, Fatima (Nutrition & Cancer, 2011)
Our aim was to investigate the effect of several dietary polyphenols on uptake of 14C-butyrate (14C-BT) by Caco-2 cells and try to correlate this effect with the modulation of the anticarcinogenic effect of BT in these cells. Acutely, uptake of 14C-BT (10 μM) was decreased by resveratrol, quercetin, myricetin, and chrysin, and increased by xanthohumol, catechin, and epicatechin; and uptake of 14C-BT (20 mM) was reduced by resveratrol, quercetin, myricetin, chrysin, EGCG, and epicatechin. Resveratrol acts as a competitive inhibitor of 14C-BT uptake. Chronically, quercetin and EGCG increased uptake of 14C-BT (10 μM), whereas myricetin, rutin, chrysin, and xanthohumol decreased it. Moreover, catechin (1 μM), quercetin, myricetin, rutin, EGCG, and chrysin increased uptake of 14C-BT (20 mM), whereas catechin (0.1 μM) decreased it. EGCG, myricetin, and catechin decreased MCT1 mRNA expression, while chrysin increased it; quercetin, rutin, and xanthohumol had no effect. BT (5 mM; 48 h) markedly decreased cellular viability and proliferation and increased cell differentiation and apoptosis. In general, combination of polyphenolic compounds with BT did not significantly modify these changes. In conclusion, changes in uptake of BT induced by polyphenols do not correlate with changes on the effect of BT upon cell viability, cell proliferation, differentiation, and apoptosis.